2019
DOI: 10.1128/mra.01699-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of an Anaerobic Benzene-Degrading Bacterium, Azoarcus sp. Strain DN11

Abstract: Here, we present the complete genome sequence of Azoarcus sp. strain DN11, a denitrifying bacterium capable of anaerobic benzene degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…toluolicum, and Ar. toluvorans, together with the “Azoarcus” strains CIB and DN11 [ 20 , 37 ]. Aromatoleum diolicum sits just outside Group 2, and the strain KH32C appears not to belong to either group, but is slightly closer to the Aromatoleum Group 2 than to Group 1.…”
Section: Resultsmentioning
confidence: 99%
“…toluolicum, and Ar. toluvorans, together with the “Azoarcus” strains CIB and DN11 [ 20 , 37 ]. Aromatoleum diolicum sits just outside Group 2, and the strain KH32C appears not to belong to either group, but is slightly closer to the Aromatoleum Group 2 than to Group 1.…”
Section: Resultsmentioning
confidence: 99%
“…Other bacteria belonging to Betaproteobacteria , Azoarcus sp. strain KH32C [ 52 ], DN11 [ 53 ], and CIB [ 54 ] isolated from agricultural fields of paddy rice and soybean, gasoline-contaminated groundwater, and culture medium of another Azoarcus strain, respectively, have similar genes to the MHCR gene cluster in the MAG ISEC-1. Although these Azoarcus strains have not been identified as EAMs, previous studies have shown that Azoarcus members are the predominant components of electroactive microbial communities in several bioelectrochemical enrichments [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Successful isolates using nitrate as an electron acceptor and capable of benzene degradation include Azoarcus species isolated from gasoline-contaminated groundwater in Kumamoto, Japan (Kasai et al, 2006). The genome of the benzene-degrading Azoarcus strain DN11 was later published by Devanadera et al (2019). In addition, a strain of the species Bacillus cereus growing on benzene under nitrate-reducing was isolated by screening procedure from gasoline-contaminated soil (Dou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%